2015
DOI: 10.1039/c4cp04944f
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical molecular dynamics of bovine serum albumin in concentrated aqueous solution below and above thermal denaturation

Abstract: The dynamics of proteins in solution is a complex and hierarchical process, affected by the aqueous environment as well as temperature. We present a comprehensive study on nanosecond time and nanometer length scales below, at, and above the denaturation temperature Td. Our experimental data evidence dynamical processes in protein solutions on three distinct time scales. We suggest a consistent physical picture of hierarchical protein dynamics: (i) self-diffusion of the entire protein molecule is confirmed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
96
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(104 citation statements)
references
References 81 publications
8
96
0
Order By: Relevance
“…The authors identified one component with the translation and rotation of the entire protein, after finding it quantitatively consistent with theories of effective colloidal hard spheres, for all temperatures where the protein is in its native conformational state. Above the denaturation temperature T d , the corresponding diffusion coefficient was found to drop, consistent with the result by Hennig et al (2012), indicating that the motion of the entire macromolecule is strongly obstructed by cross-linking or entanglement (Grimaldo et al, 2015a). The two remaining processes were associated with internal dynamics and interpreted in terms of a model of two switching diffusive states.…”
Section: Comparison Of Internal Protein Dynamics In Native Molten Ansupporting
confidence: 78%
See 1 more Smart Citation
“…The authors identified one component with the translation and rotation of the entire protein, after finding it quantitatively consistent with theories of effective colloidal hard spheres, for all temperatures where the protein is in its native conformational state. Above the denaturation temperature T d , the corresponding diffusion coefficient was found to drop, consistent with the result by Hennig et al (2012), indicating that the motion of the entire macromolecule is strongly obstructed by cross-linking or entanglement (Grimaldo et al, 2015a). The two remaining processes were associated with internal dynamics and interpreted in terms of a model of two switching diffusive states.…”
Section: Comparison Of Internal Protein Dynamics In Native Molten Ansupporting
confidence: 78%
“…Depending on data statistics, simultaneous fitting of several q values can be used to achieve reliable results for the chosen model parameter, as e.g. proven successfully by Grimaldo et al (2015a). We remark that the flexibility to choose the specific form of Γ 1,2 (q) as well as the switching time distributions for τ 1,2 allows to model processes ranging from simple diffusion and Ornstein-Uhlenbeck processes to continuous time random walks (Roosen-Runge et al, 2016).…”
Section: Localized Internal Dynamicsmentioning
confidence: 99%
“…ref. 47 and references therein). This demonstrates that internal diffusive motions in proteins on the picosecond timescale are governed by H-bonding and depend weakly on the secondary structure content.…”
Section: Internal Protein Diffusive Motionsmentioning
confidence: 99%
“…From the physical point of view, a rise in temperature results in hydrogen bond weakening and strengthening of hydrophobic interactions, 6 and also in a significant alteration of diffusion and accessibility of protein side-chains. 7 Temperature-induced aggregation is observed for all proteins in their native state: at a certain temperature protein globules start to melt, and the association of unfolded intermediates becomes energetically favorable. Kinetic and energetic aspects of this process, as well as the corresponding structural transitions, are widely investigated using numerous techniques, 8 including small angle X-ray and neutron scattering (SAXS and SANS, respectively), which provide information on the structure and interactions of proteins in solution.…”
Section: Introductionmentioning
confidence: 99%